2015
DOI: 10.1590/0074-02760150262
|View full text |Cite
|
Sign up to set email alerts
|

Waterborne toxoplasmosis investigated and analysed under hydrogeological assessment: new data and perspectives for further research

Abstract: We present a set of data on human and chicken Toxoplasma gondii seroprevalence that was investigated and analysed in light of groundwater vulnerability information in an area endemic for waterborne toxoplasmosis in Brazil. Hydrogeological assessment was undertaken to select sites for water collection from wells for T. gondii oocyst testing and for collecting blood from free-range chickens and humans for anti-T. gondii serologic testing. Serologic testing of human specimens was done using conventional commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 34 publications
2
34
0
1
Order By: Relevance
“…cut-off (Table 1), all other prevalences calculated using positivity against TgERP presented considerable disparities with prevalence calculated by IgG (alone or together with IgM) detected by commercial kits. Nonetheless, the present study indeed confirms the importance of oocyst infection contributing to the overall prevalence of toxoplasmosis in endemic settings as shown in Table 1 and Figure 2(a, b) and reported previously [30]. To the best of our knowledge this is the first report on salivary IgA against sporulated oocyst antigens.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…cut-off (Table 1), all other prevalences calculated using positivity against TgERP presented considerable disparities with prevalence calculated by IgG (alone or together with IgM) detected by commercial kits. Nonetheless, the present study indeed confirms the importance of oocyst infection contributing to the overall prevalence of toxoplasmosis in endemic settings as shown in Table 1 and Figure 2(a, b) and reported previously [30]. To the best of our knowledge this is the first report on salivary IgA against sporulated oocyst antigens.…”
Section: Discussionsupporting
confidence: 92%
“…However, when our group used the same threefold s.d. criteria to evaluate serological IgG positivity against TgERP in a previous study, we identified patients presenting that profile [30]. We have proposed a possible explanation for that based on the vast genetic diversity of parasites in South America compared to the lower genetic diversity of parasites reported in North America and Europe [35].…”
Section: Discussionmentioning
confidence: 99%
“…Wild foxes often have high seroprevalences of T. gondii with for example, 35% seroprevalence found in populations in Austria (52) and 100% in Czech Republic (53). This is consistent with high levels of exposure to the parasite often seen in human populations: for example in Brazil, human population seroprevalence can reach up to 80-90% (54,55), in France 89% (56) and in Northern Ireland 85% (57). Wild foxes also have longer lifespans relative to the commonly studied rodent animal models, allowing time for the accumulation of by-product effects of neurotropic infection that are seen in humans.…”
Section: Introductionmentioning
confidence: 66%
“…In pregnant women, toxoplasmosis is acquired through the consumption of undercooked meat infected with cysts, or through oocysts infecting vegetables or water in nature. In Brazil, serologic testing has suggested the possibility of infection through drinking water [6]. This last route of infection certainly deserves more attention with respect to prevention and clinical consequences.…”
Section: Natural History Of Congenital Toxoplasmosismentioning
confidence: 99%